Demographical Ageing of the EU Member States’ Societies - Ewa Wasilewska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
A spatial differentiation of the level of demographical senility was illustrated in the study, along with determination of dynamics of the European Union Member States ageing process (EU 27). The research period included years 1996-2016. The measures of demographical senility were used in the static and dynamical aspect. Country grouping due to the level of demographical senility advancement was performed based on statistical measures. A significant differentiation of the demographical senility level and population ageing process in the spatial system were found. The highest degree of demographical senility advancement was observed in the countries of “the old” Union but the greatest dynamics of this process was shown in the case of new Member States, including Poland and Baltic States.